The kernel space of linear operator for a class of Grushin equation - Wei, Yawei; Zhou, Xiaodong (Topological Methods in Nonlinear Analysis, 2025)
In this paper, we concern the kernel of linear operator for a class of Grushin equation.First, we study the kernel space of linear operator for a general Grushin equation.Then, we provide an exact expression for the kernel space of linear operator associated with a special Grushin equation.Finally, we prove the linear operator related to the singularly perturbed Grushin equation is invertible when restricted to the complement of its approximate kernel space.